Ресурсний потенціал сільських територій та ефективність його використання - Бурова, Ольга Борисівна (НУБіП України, 2015)
Дисертація на здобуття наукового ступеня кандидата економічних наук за спеціальністю 08.00.03 – економіка та управління національним господарством. – Національний університет біоресурсів і природокористування України, Київ, 2015. У дисертаційній роботі розроблено теоретико-методичні засади та практичні рекомендації щодо ефективного використання ресурсного потенціалу сільських територій регіону. Обґрунтовано соціально-економічну сутність ресурсного потенціалу сільських територій, визначено та доповнено його структуру. Проаналізовано сучасний стан соціально-демографічного, економічного потенціалів сільських територій, що дозволило здійснити оцінку узгодженості між ними та спрогнозувати рівень використання ресурсного потенціалу при наявних умовах. Розраховано інтегральний індекс забезпеченості сільського населення об’єктами соціально-культурного призначення. Розроблено рекомендації щодо розвитку сільського зеленого туризму як передумови ефективного використання ресурсного потенціалу сільських територій. На підставі результатів проведеного дослідження обґрунтовано напрями державної підтримки розвитку сільських територій регіону з урахуванням європейських стандартів на основі диверсифікації економічної діяльності сільських громад і розвитку сільськогосподарської обслуговуючої кооперації.
The dissertation to obtain a scientific degree of the candidate of economic sciences on speciality 08.00.03 – economy and management of the national economy. – National University of Life and Environmental Sciences of Ukraine, Kyiv, 2015. In this dissertation theoretical and methodological principles and practical recommendations for the effective use of the resource potential of rural areas of the region are developed. Social and economic essence of the resource potential of rural areas is justified; its structure is defined and supplemented. As a result of theoretical generalizations it has been proved that the category of "resource potential of rural areas" is a set of primary (natural, economic, social) and secondary (manufacturing, labor, financial, environmental and other) resources, effective use of which best satisfies the needs of the rural population in the economic and social benefits. The structural model of the resource potential of rural areas at the micro level has been formed; this model is confirmed by the feasibility of systematization of the components of natural and resource potential and its supplementations with economic and social units. It is revealed that components of these units are closely interrelated and significantly affect the efficient use of the resource potential of rural communities. The current state of socio-demographic, economic potential is analyzed; and the effect of the resource potential on the living standards of the rural population is evaluated, which allowed us to predict the level of its use under the existing conditions. Based on the results of our calculations of the unit of economic potential indicators, which significantly affect the level of efficiency of the resource potential of rural areas of the region, the output growth of gross agricultural production, profit, productivity, assets and some other tendencies were detected. However, despite this, there is a significant reduction of living standards, incomes of the population, especially for the lowest wage in agriculture. The results of the research suggested the methodological approaches to assessing the level of efficiency of resource potential with the aim of increasing social orientation of rural development based on the algorithm of consistency between the levels of development of social and economic potentials. The held grouping of districts by population density showed that the feature of the settlement in the Kherson region is the localization of urban and rural population in the Dnieper, suburban and Black Sea areas. On the basis of correlation and regression analysis of fertility in the study area, we found that the coverage of children with preschool establishments and wages level in the region affect the effective index least of all, and the incidence of rural population and the presence of men in rural areas affect it most. On this basis the approaches to the formation of strategy of social development of rural territories of the Kherson region has been developed; its activities are aimed at preserving human potential by reducing unemployment and reforming health care in rural areas. The integral index of the rural population by socio-cultural destination for its optimization has been calculated. Taking into account peculiarities of the studied region, Kherson region, the recommendations for the development of rural eco-tourism as a prerequisite for effective use of the resource potential of rural areas have been developed. The conducted SWOT analysis of the socio-economic development of rural areas of the region shows that in Kherson region significant resource potential is available. It is the region of the largest in Ukraine provision of land and plowed farmland, with unique recreational potential and opportunities for development of rural green tourism, where the agricultural production is predominant. At the same time, there are threats of rural areas, as the monotony of agricultural landscapes, land degradation, inefficient use, and weak diversification of production, as well as reduced income and living standards of the rural population. The mechanism of creation of tourism networks in the field of green tourism is improved, this involves the use of internal and external sources of funding, the sustainability of tourism services, the development of social infrastructure in rural areas, the development of a set of activities, which would level the seasonality of tourist services. It is proved that the efficient use of the resource potential of rural areas in the context of their social and economic development must be achieved by the simultaneous agreement of levels of the development of their economic and social potentials. This requires coordination and selection of a limited number of objects (districts of rural areas of the region), where it can be most effective. Such objects should be selected on the basis of the proposed integrated assessment of the level of use of the resource potential of rural areas of Kherson region. A significant argument for improving the efficiency of resource potential is the development of agricultural service cooperatives, which should be implemented in the following areas: amendments to legislative acts in terms of determining service cooperatives as non-profit organizations; comprehensive (financial, organizational, informational and other support by the state; the formation of skilled workers (managers, economists, accountants and leaders who will participate in the development of cooperatives in rural areas; the promotion of cooperative ideas at the state and local levels. In the center of this reform there must be a villager, who should be given decent living conditions according to the European standards, and it should be a key priority of the new state policy of Ukraine. Based on the results of the conducted research work, there were suggested the directions of the state support of socio-economic development of rural areas of the region, taking into account European standards, which include: improving the efficiency of agricultural production, creating new jobs, increasing farmers' incomes, increasing funding for social quantitative and qualitative improvement of social services, increased revenue from rural eco-tourism and agricultural service cooperatives in local budgets, provision of market participants, including the provision of consultative services for Advisory services, implementation of anti-corruption policies at all hierarchical levels.
Keywords: сільська територія; ресурсний потенціал сільських територій; економічний потенціал; соціальний потенціал; соціально-економічний розвиток сільських територій; сільськогосподарське виробництво; диверсифікація; сільський зелений туризм; сільськогосподарська обслуговуюча кооперація; державна підтримка; rural area; he resource potential of rural areas; economic capacity; social capacity; ocial and economic development of rural areas; agricultural production; diversification; rural eco-tourism; agricultural servicing cooperatives; tate support